2023
DOI: 10.3390/su15021386
|View full text |Cite
|
Sign up to set email alerts
|

Educational Mechatronics Training System Based on Computer Vision for Mobile Robots

Abstract: Boosting by the world’s context, several efforts have been maiden toward the digital transformation of Education. Technology-based active learning has become pivotal in pursuing a more flexible education system. This work presents the development of an Educational Mechatronics (EM) training system based on computer vision that performs as a positioning system for mobile robots in the 2D plane. The results show that the obtained precision, exactitude, and resolution of the EM training system are suitable for ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As a consequence of computational vision's importance not only in industry but supporting the day-to-day activities of a large part of society, a lot of effort has been focused on improving undergraduate student training to provide the specialized knowledge that technological companies require for the development of such sophisticated systems [3,16,20,40,46]. According to Hernandez-de-Menendez et al [21], there are nine technological advances that are currently supporting the so-called Industry 4.0: autonomous robots, simulation, horizontal and vertical system integration, industrial internet of things, cybersecurity, the cloud, additive manufacturing, augmented reality, and big data and analytics.…”
Section: Related Workmentioning
confidence: 99%
“…As a consequence of computational vision's importance not only in industry but supporting the day-to-day activities of a large part of society, a lot of effort has been focused on improving undergraduate student training to provide the specialized knowledge that technological companies require for the development of such sophisticated systems [3,16,20,40,46]. According to Hernandez-de-Menendez et al [21], there are nine technological advances that are currently supporting the so-called Industry 4.0: autonomous robots, simulation, horizontal and vertical system integration, industrial internet of things, cybersecurity, the cloud, additive manufacturing, augmented reality, and big data and analytics.…”
Section: Related Workmentioning
confidence: 99%
“…Education with the 4D Frame Mechatronics Kit is possible to realize at different levels of education. In Guerrero-Osuna, Nava-Pintor, Olvera-Olvera, Ibarra-Pérez, Carrasco-Navarro and Luque-Vega (2023) [55], referring to engineering education in the bachelor stage of study, showed how it is possible to implement Seymour Papert's constructionism [34] and technology integration in education. Additionally, in our case, the students-future teachers for primary education according to the mentioned study in the following presented activities-actively constructed their knowledge from their experiences and interactions with the environment and set 4D Frame Mechatronics Kit.…”
Section: Procedures Of Activitiesmentioning
confidence: 99%
“…In this sense, previous works [29][30][31][32] have considered this factor and have made significant efforts to develop educational tools that incorporate a well-defined learning methodology. The authors have strongly emphasized creating tools that promote active learning.…”
Section: Related Workmentioning
confidence: 99%